2009
DOI: 10.1152/ajpheart.00555.2009
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular pacing improves right heart function in experimental pulmonary arterial hypertension: a study in the isolated heart

Abstract: Right heart failure in pulmonary arterial hypertension (PH) is associated with mechanical ventricular dyssynchrony, which leads to impaired right ventricular (RV) function and, by adverse diastolic interaction, to impaired left ventricular (LV) function as well. However, therapies aiming to restore synchrony by pacing are currently not available. In this proof-of-principle study, we determined the acute effects of RV pacing on ventricular dyssynchrony in PH. Chronic PH with right heart failure was induced in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 35 publications
(46 reference statements)
5
52
0
1
Order By: Relevance
“…Male Wistar rats were used (150 to 175 g, 30 in total), and experimental PH was induced by monocrotaline (60 mg/kg). 9,18 …”
Section: Methodsmentioning
confidence: 99%
“…Male Wistar rats were used (150 to 175 g, 30 in total), and experimental PH was induced by monocrotaline (60 mg/kg). 9,18 …”
Section: Methodsmentioning
confidence: 99%
“…However, these patients display a ''LHF-like'' dyssynchrony due to a complete right bundle branch block as a (late) complication of cardiac surgery and are, therefore, not representative for the PAH population in general. We recently explored the clinical potential of resynchronisation therapy in an experimental model of PAH-induced right heart failure, in the absence of conduction disturbances [84]. We found that pre-excitation of the RV free wall resulted in improved RV systolic function and reduced adverse LV diastolic interaction.…”
Section: Cardiac Resynchronisation Therapymentioning
confidence: 99%
“…However, we recently demonstrated that LV and RV dyssynchrony are essentially different: the origin of PAH-related ventricular dyssynchrony lies in regional differences in the duration of the contraction, rather than regional differences in onset of the contraction (e.g. due to a conductance delay); and is highly afterload dependent [83,84].…”
Section: Cardiac Resynchronisation Therapymentioning
confidence: 99%
“…54 In an animal model of RV failure, the improvement in RV function could be produced by RV free wall pre-excitation. 52 An acute study of 67 patients with pulmonary artery hypertension showed enhancement of RV contractility by CRT. 55 To date, there have been very few studies of the longterm benefit of CRT in these patients and their associated response rate.…”
Section: Other Potential Crt Indicationsmentioning
confidence: 99%